2003
DOI: 10.1086/379772
|View full text |Cite
|
Sign up to set email alerts
|

Acute Human Immunodeficiency Virus Infection in Patients Presenting to an Urban Urgent Care Center

Abstract: Acute infection with human immunodeficiency virus (HIV) is often accompanied by a flu-like illness, and early identification and treatment may help control the infection and prevent transmission. We enrolled patients who presented to an urban urgent care center with any symptoms of a viral illness and any recent potential risk for HIV infection, and we tested them for acute HIV infection using enzyme-linked immunosorbent and RNA assays. Of 499 patients enrolled over a 1-year period, acute HIV infection was dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 30 publications
1
39
0
1
Order By: Relevance
“…Since acute retroviral syndromes mimic many common febrile illnesses, including infectious mononucleosis, influenza, malaria, and rickettsial diseases (1,10), the true diagnosis (acute HIV) is rarely considered at an initial patient encounter (1,(10)(11)(12). The diagnostic challenge in acute HIV infection is made more difficult by the fact that routine HIV antibody tests will typically remain negative for 1-2 weeks beyond the onset of acute retroviral symptoms (26-35 days following initial infection) (5, 13); additional virus-specific diagnostic tests (e.g., HIV p24 antigen ELISA and HIV nucleic acid amplification assays) are needed to detect HIV infection prior to the appearance of antibodies ( Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since acute retroviral syndromes mimic many common febrile illnesses, including infectious mononucleosis, influenza, malaria, and rickettsial diseases (1,10), the true diagnosis (acute HIV) is rarely considered at an initial patient encounter (1,(10)(11)(12). The diagnostic challenge in acute HIV infection is made more difficult by the fact that routine HIV antibody tests will typically remain negative for 1-2 weeks beyond the onset of acute retroviral symptoms (26-35 days following initial infection) (5, 13); additional virus-specific diagnostic tests (e.g., HIV p24 antigen ELISA and HIV nucleic acid amplification assays) are needed to detect HIV infection prior to the appearance of antibodies ( Figure 1).…”
mentioning
confidence: 99%
“…Pincus and colleagues (12) found that five (1.0%) of 511 consecutive urgent-care-center attendees with "any viral symptoms" in Boston had acute HIV infection confirmed by seroconversion. Rosenberg and colleagues examined specimens submitted for heterophile antibody testing for infectious mononucleosis in a university hospital and found that at least four (0.8%) of 536 sera examined were from acutely HIV-infected patients (11).…”
mentioning
confidence: 99%
“…The only previous study to develop a prevalence estimate was a prospective study of 499 patients visiting an urban urgent care center in Boston. 10 The prevalence was 1%…”
Section: Discussionmentioning
confidence: 98%
“…One recent prospective PREVALENCE OF PRIMARY HIV INFECTION study determined a prevalence of 1% for patients with viral symptoms and at least 1 risk factor seeking care at an urban urgent care center, a setting in which a high prevalence of HIV infection is expected. 10 Other studies have concluded that no symptom is suffi ciently sensitive and specifi c to allow for targeted testing. 4,5 It is diffi cult to determine which persons have a substantial probability of primary HIV infection when evaluating risk factors alone.…”
Section: Introductionmentioning
confidence: 99%
“…The nonspecific nature of these symptoms poses a major challenge for diagnosis, and emphasizes the need to obtain an accurate history of possible HIV exposure. For example, primary HIV infection should be considered in any patient with possible exposure presenting with fever of unknown cause (Pincus, JM., et al, 2003). This was especially pronounced in episodic care settings, such as STD clinics, emergency departments and urgent care facilities.…”
Section: Discussion and Commentsmentioning
confidence: 99%